Expression of a rice chitinase gene in transgenic banana (‘Gros Michel’, AAA genome group) confers resistance to black leaf streak disease - Kovács, Gabriella (Springer Netherlands, 2012)
Transgenic banana (Musa acuminata ‘Gros Michel’) integrating either of two rice chitinase genes was generated and its resistance to Black Leaf Streak disease caused by the fungus Mycosphaerella fijiensis was tested using a leaf disk bioassay. PCR screening indicated the presence of the hpt selectable marker gene in more than 90 % of the lines tested, whereas more than three quarters of the lines contained the linked rice chitinase gene resulting in a co-transformation frequency of at least 71.4 %. Further, a unique stable integration of the transgenes in each line revealed some false negative PCR results and the expected co-transformation frequency of 100 %. The transgene insert number per line ranged from 1 to 5 and single transgene insert lines (25 % of all) were identified. Considerable delay in disease development (up to 63 days post-incoculation) over a monitoring period of 108 days occurred in nine lines with extracellularly targeted chitinase out of 17 transgenic lines tested and their necrotic leaf area decreased by 73–94 % compared to the untransformed susceptible control line. Finally, correlation between symptom development and rice chitinase expression was confirmed in two lines by Western analysis. The potential of rice chitinase genes to enhance resistance against M. fijiensis in banana was demonstrated as well as the usefulness of the leaf disk bioassay for early disease screening in transgenic banana lines. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11248-012-9631-1) contains supplementary material, which is available to authorized users.